PICTOGRAM ON SIGNAGE AS AN EFFECTIVE COMMUNICATION - Siti Clara; Wirania Swasty (Jurnal Sosioteknologi, 2017)
Pictograms on signage may convey information or convey regulatory and prohibitory which are easily understood briefly by visitors from any circles. Problems identified is Museum of Lampung does not currently have a pictogram on any signage. Therefore, the design of pictograms on signage for the Museum of Lampung is important to communicate information briefly and effectively. This study use qualitative and quantitative approach. Literature review; observation to three similar museums, interview and questionnaires are conducted to collect data. Three similar objects are compared to get analysis data. The result shows that the pictogram is one of the informative signage elements that are important to clarify the information without having to read the text.  This study proposes pictogram on signage for the Museum of Lampung with a visual concept by adopting identity of Lampung i.e. siger and tapis pattern. The aim of this study is to show the importance of using pictograms in graphic communication. It is expected the effective pictogram on signage will be able to communicate the necessary information and easy to understand immediately without using a lot of text.